3D reconstruction of marble shipwreck cargoes based on underwater multi-image photogrammetry. Issue 1 (2016) - Balletti, C.; Beltrame, C.; Costa, E.; Guerra, F.; Vernier, P.
Abstract: Acquisition and processing of point clouds, allowing the high dimensional accuracy that is an essential prerequisite for good documentation, are widely used today for cultural heritage surveys. In recent years, manual and direct surveys in archaeological survey campaigns have been replaced by digital image processing and laser-scanning. Multi-image photogrammetry has proven to be valuable for underwater archaeology. A topographical survey is always necessary to guarantee dimensional accuracy, and is necessary for geo-referencing all the finds in the same reference system. The need for low costs and rapid solutions, combined with the necessity of producing three-dimensional surveys with the same accuracy as classical terrestrial surveying, led the researchers to test and apply image-based techniques. Ca' Foscari and IUAV University of Venice are conducting research into integrated techniques for the accurate documentation of underwater surveys. Survey design, image acquisition, topographical measurements and data processing of two Roman shipwrecks in southern Sicily are presented in this paper. Photogrammetric and topographical surveys were organized using two distinct methods, due to the different characteristics of the cargoes of huge marble blocks, their depth and their distribution on the seabed. The results of the survey are two 3D polygonal-textured models of the sites, which can be easily used for various analyses and trial reconstructions, opening new possibilities for producing documentation for both specialists and the wider public. Furthermore, 3D models are the geometrical basis for making 2D orthophotos and cross-sections. The paper illustrates all the phases of the survey's design, acquisition and preparation, and the data processing to obtain final 2D and 3D representations. Highlights: We present the survey and representation of two Roman shipwrecks. Integrated surveying techniques for documentation of underwater sites are described. Accurate 3D models open to new analyses, reconstructions and virtual exploration.